Environment–ichthyofauna relations in a neotropical reservoir through a joint remote sensing/field sampling approach - Schmitz M.H. (2023)
© 2023 John Wiley & Sons A/S. Published by John Wiley & Sons Ltd.The damming of rivers for the formation of reservoirs causes a discontinuity in the physical and biological characteristics of the aquatic ecosystem. Changes in processes related to sedimentation and nutrients create a longitudinal gradient in water characteristics and productivity. Both the zonation and the differential distribution of primary production exert a strong influence on the other communities of these ecosystems. We hypothesised that spatiotemporal dynamics of chlorophyll-a and turbidity, driven by a longitudinal gradient, influence the ichthyofauna distribution in Sobradinho Reservoir. Using field surveys and geospatial tools, we tested the presence of a longitudinal concentration gradient for these variables, and then, its association with fish abundance (total and by trophic guilds). We used field samples between April 2008 and July 2009 and the reflectance data of Landsat 5 bands 2 and 3 to perform interpolations for each variable. The gradient was tested by extracting longitudinal profiles from the interpolation products. We tested the associations between ichthyofauna abundance and chlorophyll-a and turbidity concentrations using Spearman correlation. Sobradinho exhibited a longitudinal zonation consistent with the typical pattern of large reservoirs. Furthermore, our results highlighted the seasonal instability of this zonation. In the lacustrine zone, fish abundance was associated with seasonal productivity increase, caused by floods, whereas the fluvial zone showed lower abundances in these periods. Despite that, the fluvial zone exhibited higher fish abundance, demonstrating the common pattern for large reservoirs. The presence of favourable characteristics in this zone, such as seasonal flooding and higher environmental heterogeneity, may have corroborated the results.